The inhibition of glucose absorption of seed and pericarp extracts of Pithecellobium jiringa on intestinal tissues preparation and their phytochemical profiles - Kasmuri, Abdul Razak; Mohd Hassan, Norazian; Arifin, Syamsul; Mehat, Isa; Mat Taib, Nurhaya (2010)
The prevalence of diabetes in Malaysia within 10 years had doubled (Public Health Institute, 2008). The complication of the disease has more impact and burden on the health (ADA, 2008). The seriousness and the occurrence of the complications are closely related with tightly control hyperglycaemia (UKPDS,1998). Thus it is a better approach to screen substance that able to prevent postprandial hyperglycaemia that can cause fluctuating glucose levels i.e. to screen substance that able to decrease glucose absorption in GIT. Pithecellobium jiringa is already known to have antidiabetic property among Malaysians and used as its traditional remedy (Mohamed et al., 2005). A preliminary study showed that the plant has hypoglycaemic effect (Thevathasan, 1972). Radhiah et al. (2004) and Tungsarikarn et al. (2008) found that the plant has glucose lowering effect and the latter also proved the plant extract has an effect on alpha-glucosidase enzyme. On the other hand the seeds containing djenkolic acid which can cause djenkolism, which is a toxicity effect characterized by acute renal failure, urinary obstruction and spasmodic pain (Barceloux, 2009). The study was conducted with the aim at elaborating and reconciling the previous finding on the glucose lowering effect of P. jiringa. In order to make it more explorative, both of the seed and pericarp extracts of the plant were studied.